Photocatalytic Decolorization of Celestine Blue B from Industrial Wastewater Using Ni3O4-MgO Coupled Oxides - Kahdum, Salih H.; Karaem, Mohannad M.; Hussein, Abbas O.; Esmael, Hussein E.; Kahdum, Kuhdair J.; Atiyah, Abbas J. (Asian Journal of Chemistry, 2018)
This study describes the preparation of coupled oxide Ni3O4-MgO using co-precipitation method using their corresponding nitrates as precursor materials to prepare these coupled oxides. The prepared oxides were investigated with X-ray diffraction and Fourier transform infrared spectroscopy. The photocatalytic activity of this material was investigated by following removal of Celestine blue B dye from simulated industrial wastewaters. Different reaction conditions were undertaken to reach optimum conditions for dye removal. These conditions involve performing different catalyst loading, effect of contact time and effect of pH of reaction mixture. The remaining concentration of Celestine blue B dye over the period of reaction mixture was calculated spectroscopically by measuring the absorbance of supernatant liquid at 648 nm. From the results, it was found that the optimum conditions for dye removal in this study was 0.20 g, pH 4 and a contact time of 30 min and the dye removal percentage under these conditions was found to be 89 %.